The association between hunger-coping economic tradeoffs and food insecurity among female recipients of charitable food assistance - Daphne C. Hernandez; Bo Ra Kim; Fred P. Brooks; Craig Gundersen (Appetite, 2025)

Soil Microbiome Inoculation for Resilient and Multifunctional New Forests in Post‐Agricultural Landscapes - Sofia I. F. Gomes; Per Gundersen; T. Martijn Bezemer; Davide Barsotti; Ludovica D'Imperio; Konstantinos Georgopoulos; Mathias Just Justesen; Karelle Rheault; Yamina M. Rosas; Inger Kappel Schmidt; Leho Tedersoo; Lars Vesterdal; et al. (Global Change Biology, 2025)
Afforestation is increasingly recognized as a critical strategy to restore ecosystems and enhance biodiversity on post‐agricultural landscapes. However, agricultural legacies, such as altered soil structure, nutrient imbalances, and depleted microbial diversity, can slow down forest establishment or cause ecosystems to deviate from expected successional trajectories. In this opinion paper, we explore the potential of soil inoculations as a tool to overcome these challenges by introducing beneficial microbial communities that can accelerate ecosystem recovery and forest development. Restoring soil biodiversity is a crucial aspect of this process that drives broader ecosystem functionality and resilience. We highlight the need to carefully consider the type and timing of inoculations and to ensure compatibility between the inoculum and recipient site characteristics to optimize the establishment of introduced species. While tree productivity is often a central focus of afforestation efforts, the restoration of soil biodiversity, which will also contribute to increased ecosystem‐level functions, should also be a priority for long‐term forest resilience. Agricultural legacies add complexities to the restoration process, creating unique challenges that need to be addressed in restoration planning. Thus, successful inoculation strategies require a thorough understanding of both donor and recipient site characteristics, also in relation to potential mismatches related to soil physiochemical properties to avoid unintended consequences such as the non‐establishment of introduced species. Additionally, we call for the re‐evaluation of afforestation targets and the development of standardized monitoring protocols that track the success of inoculation efforts, particularly regarding soil health, microbial community establishment, and biodiversity recovery. By integrating inoculation practices within a broader restoration framework, we can enhance the resilience, biodiversity, and ecosystem functionality of newly afforested landscapes. Ultimately, this approach may play a critical role in ensuring the success of large‐scale afforestation projects.

Lake browning counteracts cyanobacteria responses to nutrients: Evidence from phytoplankton dynamics in large enclosure experiments and comprehensive observational data - Anne Lyche Solheim; Hege Gundersen; Ute Mischke; Birger Skjelbred; Jens C. Nejstgaard; Alexis L. N. Guislain; Erik Sperfeld; Darren P. Giling; Sigrid Haande; Andreas Ballot; S. Jannicke Moe; Susanne Stephan; et al. (Global Change Biology, 2024)
Lakes worldwide are affected by multiple stressors, including climate change. This includes massive loading of both nutrients and humic substances to lakes during extreme weather events, which also may disrupt thermal stratification. Since multi‐stressor effects vary widely in space and time, their combined ecological impacts remain difficult to predict. Therefore, we combined two consecutive large enclosure experiments with a comprehensive time‐series and a broad‐scale field survey to unravel the combined effects of storm‐induced lake browning, nutrient enrichment and deep mixing on phytoplankton communities, focusing particularly on potentially toxic cyanobacterial blooms. The experimental results revealed that browning counteracted the stimulating effect of nutrients on phytoplankton and caused a shift from phototrophic cyanobacteria and chlorophytes to mixotrophic cryptophytes. Light limitation by browning was identified as the likely mechanism underlying this response. Deep‐mixing increased microcystin concentrations in clear nutrient‐enriched enclosures, caused by upwelling of a metalimnetic Planktothrix rubescens population. Monitoring data from a 25‐year time‐series of a eutrophic lake and from 588 northern European lakes corroborate the experimental results: Browning suppresses cyanobacteria in terms of both biovolume and proportion of the total phytoplankton biovolume. Both the experimental and observational results indicated a lower total phosphorus threshold for cyanobacterial bloom development in clearwater lakes (10–20 μg P L −1 ) than in humic lakes (20–30 μg P L −1 ). This finding provides management guidance for lakes receiving more nutrients and humic substances due to more frequent extreme weather events.

Instantaneous center of rotation in the canine femorotibial joint: Ex vivo assessment of a tool to evaluate joint stabilization surgeries - P. Mazdarani; R.S. Gundersen; J.E. Miles (Research in Veterinary Science, 2023)

Kelp Forest Distribution in the Nordic Region - Kristina Ø. Kvile; Guri Sogn Andersen; Susanne P. Baden; Trine Bekkby; Annette Bruhn; Ole Geertz-Hansen; Kasper Hancke; Jørgen L. S. Hansen; Dorte Krause-Jensen; Eli Rinde; Henning Steen; Susse Wegeberg; et al. (Frontiers in Marine Science, 2022)
Kelp forests are productive coastal ecosystems that provide a range of ecosystem services. Mapping the distribution and area occupied by kelp forests is a critical step to identify their ecosystem functions and services, including their role in the carbon cycle, and to detect changes in their distribution. We compiled quantitative data of the dominant genera Laminaria and Saccharina across the Nordic region, allowing us to separate kelp forests (areas with dense or moderately dense kelp coverage) from occurrences of single or few individuals. By fitting boosted regression trees to the compiled data, we modelled and predicted the distribution of kelp forests across the Nordic region. Despite the large scale of the analyses, the models captured well the kelps’ environmental affinities and predicted the presence of kelp forests with high accuracy. Dense kelp forests are found along the rocky shores of all the Nordic countries, except in the brackish Baltic Sea, with largest areas in Norway, Greenland and Iceland. The results of this study set the scene for future studies on the importance of kelp forests in the Nordic region, including their contribution to the marine carbon budget.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Organochlorine and Metal Contaminants in the Blood Plasma of Green Sturgeon Caught in Washington Coastal Estuaries - Julie A. Layshock; Molly A. H. Webb; Olaf P. Langness; John Carlos Garza; Laura B. Heironimus; Deke Gundersen (Archives of Environmental Contamination and Toxicology, 2022)

Status, trends and drivers of kelp forests in Europe: an expert assessment - R. M. Araújo; J. Assis; R. Aguillar; L. Airoldi; I. Bárbara; I. Bartsch; T. Bekkby; H. Christie; D. Davoult; S. Derrien-Courtel; C. Fernandez; S. Fredriksen; et al. (Biodiversity and Conservation, 2016)

Total Mercury in Six Antarctic Notothenioid Fishes - Nathan J. P. Wintle; Isaac M. Sleadd; Deke T. Gundersen; Kristina Kohl; Bradley A. Buckley (Bulletin of Environmental Contamination and Toxicology, 2015)

Soil carbon stock change following afforestation in Northern Europe: a meta‐analysis - T. G. Bárcena; L. P. Kiær; L. Vesterdal; H. M. Stefánsdóttir; P. Gundersen; B. D. Sigurdsson (Global Change Biology, 2014)
Northern Europe supports large soil organic carbon ( SOC ) pools and has been subjected to high frequency of land‐use changes during the past decades. However, this region has not been well represented in previous large‐scale syntheses of land‐use change effects on SOC , especially regarding effects of afforestation. Therefore, we conducted a meta‐analysis of SOC stock change following afforestation in Northern Europe. Response ratios were calculated for forest floors and mineral soils (0–10 cm and 0–20/30 cm layers) based on paired control (former land use) and afforested plots. We analyzed the influence of forest age, former land‐use, forest type, and soil textural class. Three major improvements were incorporated in the meta‐analysis: analysis of major interaction groups, evaluation of the influence of nonindependence between samples according to study design, and mass correction. Former land use was a major factor contributing to changes in SOC after afforestation. In former croplands, SOC change differed between soil layers and was significantly positive (20%) in the 0–10 cm layer. Afforestation of former grasslands had a small negative (nonsignificant) effect indicating limited SOC change following this land‐use change within the region. Forest floors enhanced the positive effects of afforestation on SOC , especially with conifers. Meta‐estimates calculated for the periods 30 years since afforestation revealed a shift from initial loss to later gain of SOC . The interaction group analysis indicated that meta‐estimates in former land‐use, forest type, and soil textural class alone were either offset or enhanced when confounding effects among variable classes were considered. Furthermore, effect sizes were slightly overestimated if sample dependence was not accounted for and if no mass correction was performed. We conclude that significant SOC sequestration in Northern Europe occurs after afforestation of croplands and not grasslands, and changes are small within a 30‐year perspective.

The role of colonization in the dynamics of patchy populations of a cyclic vole species - Petter Glorvigen; Gry Gundersen; Harry P. Andreassen; Rolf A. Ims (Oecologia, 2013)

Sinks for nitrogen inputs in terrestrial ecosystems: a meta‐analysis of 15 N tracer field studies - P. H. Templer; M. C. Mack; F. S. Chapin III; L. M. Christenson; J. E. Compton; H. D. Crook; W. S. Currie; C. J. Curtis; D. B. Dail; C. M. D'Antonio; B. A. Emmett; H. E. Epstein; et al. (Ecology, 2012)
Effects of anthropogenic nitrogen (N) deposition and the ability of terrestrial ecosystems to store carbon (C) depend in part on the amount of N retained in the system and its partitioning among plant and soil pools. We conducted a meta‐analysis of studies at 48 sites across four continents that used enriched 15 N isotope tracers in order to synthesize information about total ecosystem N retention (i.e., total ecosystem 15 N recovery in plant and soil pools) across natural systems and N partitioning among ecosystem pools. The greatest recoveries of ecosystem 15 N tracer occurred in shrublands (mean, 89.5%) and wetlands (84.8%) followed by forests (74.9%) and grasslands (51.8%). In the short term ( 15 N tracer application), total ecosystem 15 N recovery was negatively correlated with fine‐root and soil 15 N natural abundance, and organic soil C and N concentration but was positively correlated with mean annual temperature and mineral soil C:N. In the longer term (3–18 months after 15 N tracer application), total ecosystem 15 N retention was negatively correlated with foliar natural‐abundance 15 N but was positively correlated with mineral soil C and N concentration and C : N, showing that plant and soil natural‐abundance 15 N and soil C:N are good indicators of total ecosystem N retention. Foliar N concentration was not significantly related to ecosystem 15 N tracer recovery, suggesting that plant N status is not a good predictor of total ecosystem N retention. Because the largest ecosystem sinks for 15 N tracer were below ground in forests, shrublands, and grasslands, we conclude that growth enhancement and potential for increased C storage in aboveground biomass from atmospheric N deposition is likely to be modest in these ecosystems. Total ecosystem 15 N recovery decreased with N fertilization, with an apparent threshold fertilization rate of 46 kg N·ha −1 ·yr −1 above which most ecosystems showed net losses of applied 15 N tracer in response to N fertilizer addition.

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Three approaches to estimate wolf Canis lupus predation rates on moose Alces alces populations - Hege Gundersen; Erling J. Solberg; Petter Wabakken; Torstein Storaas; Barbara Zimmermann; Harry P. Andreassen (European Journal of Wildlife Research, 2008)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

BACULOVIRUS-BASED EXPRESSION OF AN INSECT VIRAL PROTEIN IN 12 DIFFERENT INSECT CELL LINES - Y. P. CHEN; D. E. GUNDERSEN-RINDAL; D. E. LYNN (In Vitro Cellular & Developmental Biology - Animal, 2005)

Nitrogen input together with ecosystem nitrogen enrichment predict nitrate leaching from European forests - J. A. MacDonald; N. B. Dise; E. Matzner; M. Armbruster; P. Gundersen; M. Forsius (Global Change Biology, 2002)
The IFEF database (Indicators of Forest Ecosystem Functioning), consisting of nitrogen deposition, nitrate leaching fluxes, and soil and ecosystem characteristics, is analysed to evaluate the C/N ratio in the organic horizon as an indicator of nitrate leaching. One hundred and eighty one forests are examined, from countries across Europe ranging from boreal to Mediterranean regions, encompassing broadleaf and coniferous sites and plot and catchment studies. N input in throughfall ranges from less than 1 kg N ha −1 y −1 in northern Norway and Finland to greater than 60 kg N ha −1 y −1 in the Netherlands and Czech Republic. The amount of NO 3 – leached covers a smaller range, between 1 and 40 kg N ha −1 y −1 . Nitrate leaching is strongly dependent on the amount of nitrogen deposited in throughfall (N input) and simply adding the C/N ratio in the organic horizon to a regression equation does not improve this relationship. However, when the data are stratified based on C/N ratios less than or equal to 25 and greater than 25, highly significant relationships ( P 3 – leached. The slope of the relationship for those sites where C/N ratio is ≤ 25 (′nitrogen enriched′ sites) is twice that for those sites where C/N ratio is > 25. These empirical relationships may be used to identify which forested ecosystems are likely to show elevated rates of nitrate leaching under predicted future nitrogen deposition scenarios. Elevated NO 3 – leaching also shows a relationship with soil pH, with high rates of NO 3 – leaching only observed at sites with a pH 30 kg N ha −1 y −1 . Tree age and species have no significant impact on the ecosystem response to N input at a regional scale.

Maximum rates of N 2 fixation and primary production are out of phase in a developing cyanobacterial bloom in the Baltic Sea - J. R. Gallon; A. M. Evans; D. A. Jones; P. Albertano; R. Congestri; B. Bergman; K. Gundersen; K. M. Orcutt; K. von Bröckel; P. Fritsche; M. Meyerhöfer; K. Nachtigall; et al. (Limnology and Oceanography, 2002)
Although N 2 ‐fixing cyanobacteria contribute significantly to oceanic sequestration of atmospheric CO 2 , little is known about how N 2 fixation and carbon fixation (primary production) interact in natural populations of marine cyanobacteria. In a developing cyanobacterial bloom in the Baltic Sea, rates of N 2 fixation (acetylene reduction) showed both diurnal and longer‐term fluctuations. The latter reflected fluctuations in the nitrogen status of the cyanobacterial population and could be correlated with variations in the ratio of acetylene reduced to 15 N 2 assimilated. The value of this ratio may provide useful information about the release of newly fixed nitrogen by a cyanobacterial population. However, although the diurnal fluctuations in N 2 fixation broadly paralleled diurnal fluctuations in carbon fixation, the longer‐term fluctuations in these two processes were out of phase.

Individual and population level determinants of immigration success on local habitat patches: an experimental approach - Gry Gundersen; Harry P. Andreassen; Rolf A. Ims (Ecology Letters, 2002)
The effect of population density on immigration success of young root voles was studied in a factorial experiment where immigrants of three different types were translocated from donor populations to recipient habitat patches with experimentally manipulated population sizes. The different types of immigrants were: (1) residents, animals that had remained in their natal patch; (2) colonists, animals that already had successfully dispersed and settled in a new patch; and (3) transients, animals roaming around in a non‐habitable matrix area of the donor population. Generally, we found evidence for a negative density‐dependent immigration success in terms of survival, rate of sexual maturation and body growth rate. With respect to the survival rate, the degree of density dependence differed among the three immigrant types. Our findings are discussed with respect to the degree of rescue effect immigrants may have on a recipient population depending on population density, and also its relevance concerning translocation of individuals for conserving endangered populations.

Synthesis of Nitrogen Pools and Fluxes from European Forest Ecosystems - N.B. Dise; E. Matzner; P. Gundersen (Water, Air, & Soil Pollution, 1998)

Predicting the Effects of Atmospheric Nitrogen Deposition in Conifer Stands: Evidence from the NITREX Ecosystem-Scale Experiments - B. A. Emmett; D. Boxman; M. Bredemeier; P. Gundersen; O. J. Kjønaas; F. Moldan; P. Schleppi; A. Tietema; R. F. Wright (Ecosystems, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)